Pharmacokinetics and Withdrawal Times of Enrofloxacin in Ducks - Natthasit Tansakul; Amnart Poapolathep; Naruamol Klangkaew; Napasorn Phaochoosak; Wanida Passudaruk (Agriculture and Natural Resources, 2005)
The pharmacokinetic properties of enrofloxacin (EFX) were investigated in healthy ducks following a single administration of EFX with a dose of 10 mg/kg of body weight by intravenous (i.v.), intramuscular (i.m.), subcutaneous (s.c.) or oral (p.o.) route. The plasma concentration-time curve was analyzed using a two compartment model. Mean peak plasma concentration of EFX was 11.49 ± 1.17, 5.65 ± 0.36, 4.99 ± 0.87 and 4.87 ± 0.69 mg/ml after i.v., i.m., s.c. and p.o. administration, respectively. After a single i.v. administration, the pharmacokinetic parameters were found as follow; the elimination half-life (t1/2β) = 6.47 ± 2.85 h, the elimination rate constant (Kel ) = 0.70 ± 0.06 h-1,the apparent volume of distribution Vd(area) = 1.30 ± 0.22 L/kg and the total body clearance (ClB) = 0.89 ± 0.07 L/kg/h. Difference enrofloxacin bioavailability following i.m., s.c. and p.o. administration were 98.77 ± 0.05 %, 85.11 ± 2.71 % and 80.35 ± 0.29%, respectively. The results of pharmacokinetic properties of EFX in ducks should be provided with the dosage regimen, preslaughter withdrawal times and maximum residue limits for ducks.